PERANCANGAN TEBAL DAN ESTIMASI BIAYA PERKERASAN KAKU (RIGID PAVEMENT) PADA PROYEK PEMELIHARAAN JALAN KOLEKTOR DI JALAN MADUKARA KABUPATEN CILACAP - , SIMPLISIUS AMBOT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Construction of new roads or the maintenance of roads that have been damaged in connection with the addition of road capacity is needed. Design method is effective and efficient on a pavement planning is absolutely necessary as the collector road maintenance on roads Madukara Jeruklegi Cilacap district. Goal of designing an effective and efficient than a pavement that is cost effective with minimum pavement thickness but fulfills the safety of road users. Data needs to make pavement design obtained from direct retrieval or data that has been there before and then analyzed by standard cement concrete pavement design in order to obtain results that meet the requirements of the planning standards. From the analysis of cement concrete pavement design pavement thickness of 180 mm is obtained at a cost of Rp. 416.044.000,00